Sulfonation of papain-treated chitosan and its mechanism for anticoagulant activity - Jiraporn Suwan (2018)
The novel low-molecular-weight chitosan polysulfate (MW 5120-26,200 Da) was prepared using the depolymerization of chitosan with papain (EC. 3.4.22.2). The sulfonation of depolymerized products was performed using chlorosulfonic acid in N,N-dimethylformamide under semi-heterogeneous conditions. The structures of the products were characterized by FTIR,13C NMR, and1H NMR (1D, 2D NMR) spectroscopy. The present study sheds light on the mechanism of anticoagulant activity of chitosan polysulfate. Anticoagulant activity was investigated by an activated partial thromboplastin assay, a thrombin time assay, a prothrombin time assay, and thrombelastography. Surface plasmon resonance also provided valuable data for understanding the relationship between the molecular binding of sulfated chitosan to two important blood clotting regulators, antithrombin III and heparin cofactor II. These results show that the principal mechanism by which this chitosan polysulfate exhibits anticoagulant activity is mediated through heparin cofactor II and is dependent on polysaccharide molecular weight. © 2009 Elsevier Ltd.